Fabricating hot embossing micro tool using electrodischarge machining - Mohammad, Ammar Sami; Ali, Mohammad Yeakub (2006)
A prototype micro tool with straight micro channels was produced on “protherm” mold material using electro discharge machining (EDM). The width and depth of the channel were 0.8 mm and 2 mm respectively. So the aspect ratio of the channel was 2.5 which was competitive with other hot embossing micro tool. This tool could be applied to emboss micro channel on heated polymer. The channel would have significant applications in biomedical and other micro-fluidic analysis. At first EDM electrode was produced with wire EDM (WEDM) process. This electrode was then used for making micro hot embossing tool using die sinking EDM technique. It produced three channels at a time.